(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
The following article discusses how memes can be considered as a teaching and learning proposal for the secondary school classroom. With this objective, a personal experience is presented in the framework of the Teaching Practice of History Teachers (Faculty of Humanities and Sciences, National University of the Littoral), designed for 4th year of an educational institution with artistic-musical orientation. In this sense, theoretical and methodological issues are addressed to pose the meme as a pedagogical device, taking into account its characterization as an ideological practice. Based on the contributions of various authors, a memetic activity for the assessment of knowledge is proposed, thus enabling a "different" history class for the secondary school classroom. Finally, three specific cases are presented for analysis, which involve controversies and various interpretations that invite the reader to think and provide their own assessments.